PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SUMBERDAYA LAHAN DI DAERAH ALIRAN SUNGAI (DAS) BONE PROVINSI GORONTALO - K. Baderan, Dewi Wahyuni (Sainstek, 2006)
The aim of this research is to see the effect of the using and the participate of society in managing resource area at Bone river stream area. The result of the research shows that the land around Bone River Stream Area (DAS) had degradated and the participate of society has showed by following training and understanding a good land conservation technique. The first thing that have done is by approaching the society especially who have the land around upstream of Bone DAS and then give them a training or ideas about a good land conservation technique. The method that has used in this research is interview, social, economic, ecological approach by giving them some questions even in individual or questioner. Based on the questioner it has found that a lot of society have given concrete answers about the problem of land resource managing, it can be seen based on the level of education, job and their motivation.